Elucidating the Biological Mechanisms Linking Depressive Symptoms With Type 2 Diabetes in Men: The Longitudinal Effects of Inflammation, Microvascular Dysfunction, and Testosterone. Issue 2 (February 2016) - Tully, Phillip J.; Baumeister, Harald; Martin, Sean; Atlantis, Evan; Jenkins, Alicia; Januszewski, Andrzej; O'Loughlin, Peter; Taylor, Anne; Wittert, Gary A.
ABSTRACT: Objective: This prospective cohort study sought to examine key biological measures linking depressive symptoms with Type 2 diabetes, specifically inflammation, microvascular dysfunction, and androgens. Methods: A cohort of 688 men without diabetes who were 35 years or older were followed up for 5 years. Venous interleukin-6, high-sensitivity C-reactive protein, sE-selectin, endogenous total testosterone, fasting glucose, and glycated hemoglobin (HbA1c) were quantified at baseline and 5 years later. Depressive symptoms were assessed using the Beck Depression Inventory-I, and men were categorized into persistent, remitted, incident, and nondepressed groups (reference). Logistic regression was used to determine odds ratios (ORs) for diabetes adjusted for propensity score calculated from 18 established risk factors. Results: Diabetes developed in 112 men (16.3% of sample). Persistent depressive symptoms were associated with diabetes (adjusted OR = 2.45, 95% confidence interval [CI] = 1.16–5.20, p = .019). Baseline testosterone (OR = 0.43, 95% CI = 0.22–0.81, p = .01) and follow-up testosterone (OR = 0.51, 95% CI = 0.31–0.84, p = .008) were inversely associated with Type 2 diabetes. Annualized HbA1c was positively associated with annualized change in cognitive Beck Depression Inventory symptoms ( β = 0.14, p = .001) and inversely associated with annualized change in testosterone ( β = −0.10, p = .014). Annualized change in fasting glucose was associated with sE-selectin ( β = 0.12, p < .001) and somatic depressive symptoms ( β = −0.12, p = .002). Conclusions: The findings suggest that lower endogenous total testosterone levels and persistent depressive symptoms were associated with Type 2 diabetes risk and HbA1c in men over a 5-year period. Abstract : Supplemental digital content is available in the text.